The Concept of Metadata - Küçük, Mehmet Emin; Al, Umut (Information World, 2001)
The Internet provides fast and effective communication. However, it has also ıntroduced several problems which can be categorised as coverage. Indexing, selection and retrieval of documents. In this descriptive study the concept of metadata, which emerged as a solution tor the problems of organising and retrieving lnternet resources, and some of the metadata creation toofs and the standards are described.